Franchising as a scalable business model: strategies for rapid revenue growth in emerging markets - Rebouças, Tuilla Magalhães de Barros (Revista ft, 2026)
Franchising has increasingly been recognized as a strategic organizational model that enables accelerated business expansion while mitigating capital constraints, particularly in emerging markets characterized by institutional volatility and heterogeneous consumer demand. This article examines franchising as a scalable business model by synthesizing contemporary literature on international franchising, entrepreneurial growth, digital transformation, and market entry strategies. The analysis explores how governance mechanisms, local asset integration, and technological adoption contribute to revenue growth and operational scalability. Evidence from bibliometric studies, empirical research, and case-based analyses indicates that franchising systems capable of balancing standardization with local responsiveness are more likely to achieve sustainable performance. The paper contributes to the academic discussion by integrating theoretical and practical perspectives on franchise expansion in developing economies, highlighting both opportunities and structural challenges associated with rapid growth strategies.